Diskursus Intelektual tentang Civil Society di Indonesia - Muhammad AS Hikam (Unisia, 1999)
It is widely believed that the Democratization movements In Chekoslovakia, Poland, East Germany and Russia, have inspired a lot of Indonesian prodemocratic activists who are today still searching for a new paradigm of political movements through the consept of civil society. However, the Indonesian Intellectual society is still arguing about the consept; some experts view it from the perspective of Hegelian and Gramscian, some others perceive it from that Tocquevellian. Never theless, it should be noted that the consept relates to the historical and socio-political backgrounds of Indonesia in order to be more helpful for civil society formation.